PP.03 Does the Apgar Score Matter? Investigating the Relationship Between a Low Score and Adverse Outcomes from Birth to Childhood. (26th April 2013) - Malin, GL; Morris, RK; Ahmad, S; Riley, R; Khan, KS
Abstract : Background: A low Apgar score at birth may occur for a variety of reasons. Existing evidence regarding the long term implications is conflicting. Methods: Systematic review of the literature, with random effects meta-analysis. Results: 87 manuscripts were included, with a total of 3, 690, 080 neonates. A low Apgar score was strongly associated with neonatal mortality in a population born at term (≥ 37 weeks gestation), or with normal birth weight (≥ 2.5 kg) (10 minute Apgar score ≤ 3: OR 1417.75, 95% CI 915.99 to 2194.36). Raising the Apgar score at a particular time reduced the strength of association. In a pre-term population, the association was smaller (10 minute score ≤ 3: OR 66.49, 95% CI 45.00 to 98.22). For neonatal morbidity, significant association was seen at a number of thresholds. In a term population, there was a significant association between a low Apgar score and cerebral palsy at all thresholds examined, with the largest association seen at a 5 minute Apgar score ≤ 3 (3 studies, OR 46.35, 95% CI 11.21 to 191.59). When the predictive ability of a low Apgar score was considered, the specificity and positive likelihood ratios were generally high, however the corresponding sensitivity and negative likelihood ratios were low. Conclusion: A low Apgar score at birth is strongly associated with neonatal mortality, morbidity and childhood cerebral palsy, particularly in a term or normal birth weight population. Further research is required to identify the threshold at which the Apgar score may best predict adverse outcomes.